The Linguistic Landscape at I Gusti Ngurah Rai International Airport, Bali: Users’ Attitudes - Ni Kade Juli Rastitiati (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2023)
This study aimed at finding out and describing the linguistic landscape (LL) at I Gusti Ngurah Rai International Airport (IGNRIA), and the users’ attitudes towards the LL. The data of LL was gathered by capturing textual forms of a language/languages by a handphone camera, while the data on users’ attitudes was collected through interviewing airport users. The users as respondents were determined based on a number of criterias, such as nationality, age and education. The result of the study showed that: 1). The LL at IGNRIA made use of 7 (seven) variations of language used, namely: a. Indonesian, b). English, c). Indonesian-English, d). English-Indonesian, e). Balinese-English, f). English-Chinese and g). Balinese script-English. 2). Regarding the attitudes towards LL, the users agreed the importance existence of LL at IGNRIA, in which bilingual Indonesian-English was used, instead of Indonesian or English written monolingually. In relation with the configurational composition, some users stated that Indonesian must be on top of English; while the others thought that either Indonesian or English can be on top, as long as it was clear and informative. Futhermore, users strongly supported the use of Balinese and Balinese Script in LL whuch may function as area identity symbol, as well as maintaining the local genius of Balinese culture. Users even stated that the use of Balinese can be a tourist attraction and knowledge which was good to learn. The use of a foreign language other than English was welcome as long as it was intended to fulfil the information needs of the airport users.